The effectiveness of aided augmented input techniques for persons with developmental disabilities: a systematic review. (3rd July 2017) - Allen, Anna A.; Schlosser, Ralf W.; Brock, Kristofer L.; Shane, Howard C.
Abstract: When working with individuals with little or no functional speech, clinicians often recommend that communication partners use the client's augmentative and alternative communication (AAC) device when speaking to the client. This is broadly known as "augmented input" and is thought to enhance the client's learning of language form and content. The purpose of this systematic review was to determine the effects of augmented input on communication outcomes in persons with developmental disabilities and persons with childhood apraxia of speech who use aided AAC. Nineteen studies met the inclusion criteria. Each included study was reviewed in terms of participant characteristics, terminology used, symbol format, augmented input characteristics, outcomes measured, effectiveness, and study quality. Results indicate that augmented input can improve single-word vocabulary skills and expression of multi-symbol utterances; however, comprehension beyond the single word level has not been explored. Additionally, it is difficult to form conclusions about the effect of augmented input on specific diagnostic populations. Directions for future research are posited.